UJI LIMBAH PADAT KELAPA SAWIT DAN PUPUK NPK 16:16:16 PADA TANAMAN ROSELLA (Hibiscus Sabdariffa. L) - Maili Sarti; T Rosmawaty; Sulhaswardi Sulhaswardi (UIR Press, 2014)
ABSTRACT The objective of this research is to examine the effect of various dosages of sludge of oil palm and NPK 16:16:16 fertiizers on growth and yield of roselle (Hibiscus safdariffa. L.). The research was carried out at the experimental farm Faculty of Agricuture Riau Islamic University Pekanbaru from May to October 2013. The competely randomized design with two factorials was used. The first factor was sludge of palm oi and the second factor was NPK 116:16:16 fertilizers. The observed parameters were plant height, flower age, harvest age, sepal number per plant, yield per plant, and number of sepal residue. Interactionally, the use of oil palm sudge of and NPK 16:16:16 fertiizers on rocella showed a significant effect on the number of flower sepal and yield per plant with the best treatment on combination of oil palm sludge with 6 kg/plot and NPK 16:16:16 fertilizers with 22.5 g/plant. Individually, the application of oil palm sludge gave a significant effect on pant height, flower age, harvesting age, sepal number per plant, yield per plant, and number of sepal residue with the best treatment on giving oil palm sludge of 6 kg/plot. The application of NPK 16:16:16 fertilizers affected significanty on plant height, flower age, harvest age, sepal number per plant, yield per plant, and number of sepal residue with the best treatment on giving NPK 16:16:16 fertilizers of 22.5 g/plant.